Validade da atual classificação das doenças periodontais (EFP/AAP 2018) em comparação com o critério CDC/AAP 2012 - um estudo transversal - Ortigara, Gabriela Barbieri (2020)
Several criteria have been used to define cases of periodontitis hampering to infer the global variation of this disease. The aim of this study was to investigate the accuracy of 2018 EFP/AAP (currrent periodontal classification) in periodontitis case definition of individuals from a rural area in southern Brazil. A population-based sample of 688 individuals, ≥15 years old, living in Rosario do Sul was investigated. A complete periodontal examination was performed at six sites/tooth, including visible plaque indice (VPI), gingival bleeding index (GBI), probing depth (PD), bleeding on probing (BOP) and clinical attachment level (CAL). Questionnaires were applied to obtain demographic and behavioral data and glycated hemoglobin (HbA1c) test were performed. The periodontitis case definition was estimated and compared according to 2018 EFP/AAP and 2012 CDC/AAP (reference criteria). Diagnostic tests such as sensitivity (SN), specificity (SP), positive predictive value (PPV), negative predictive value (NPV) and area under ROC curve (AUC) were performed. Statistical analysis was performed using Stata software (version 14.1). 588 individuals with at least 6 teeth were included. Based on 2018 EFP/AAP-findings, 71.1% individuals were classified as stage III/IV and showed 100% of agreement with 2012 CDC/AAP for severe category. For periodontitis case definition, SN of 2018 EFP/AAP were 99,8% and 100%, SP were 13,6% and 43,6%, PPV were 83,4% and 47,4% and NPV were 93,7% and 100% for moderate and severe periodontitis, respectively. The AUC was 0.9059 (95% CI = 0.879–0.933) and the optimal cutoff based on the curve was stage III. The 2018 EFP/AAP classification demonstrated high validity in the evaluation of a case of periodontitis, contributing to the improvement of diagnosis and treatment of patients with periodontal disease.